Performance Test of Cassava Cutting Machine Type of Double Block Cutter - Asmara, Sandi; Amien, Elhamida Rezkia; Warji, Warji; Tamrin, Tamrin; Rahmawati, Winda; Kurniawan, Aan; Safitri, Yuni (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Preparation of cassava seeds using a machete or hand saw takes a long time, the results are not uniform, and there is a potential for damage to cassava seedlings. The double block cutter type cassava stem cutting machine has been designed to produce high capacity and good quality cassava seeds. This study aims to test the performance of the cassava stem cutting machine with the double block cutter type. Performance tests include measuring machine working capacity, fuel consumption, seed uniformity, and planting test. The cutting test was carried out using 3 varieties of cassava seedlings. The machine works at a rotational speed of 3800 rpm and the test was carried out with various feeding loads, namely 3 rods, 4 rods, and 5 rods with. Each test was repeated 3 times. Cassava stem cutting machine (Petokong) is suitable for producing cassava stems with an average working capacity of 16275 seeds/hour. The results of the Anova test showed that the number of baits and varieties of cassava seeds and their interaction had a significant effect on the working capacity of the Petokong machine. Variations in fuel consumption are thought to be influenced by the variety of cassava stem used, which is influenced by the stem diameter of each variety. The Petokong machine is far superior to manual cutting using a machete or saw which can only produce 815 and 3005 seeds/hour per hour. The average fuel consumption is 1.82 liters per hour. Seed uniformity is about 98% and seedling damage can be minimized to 2%. The seeds produced by the Petokong machine can grow well, which is indicated by the appearance of shoots and an even distribution of roots. Â  Keywords: Cassava seeds, Cassava stem cutter, Double block cutter, Petokong